New research routes to fight myopia - González-Méijome, José Manuel (2017)
[Excerpt] Myopia can be defined optically as a failure in the ability of the eye to focus images of distance objects on the photosensitive internal layer, the retina. This can be due to excessive power of the cornea and crystalline lens, ore more commonly due to an excessive axial growth of the eyeball. In the last years, we have assisted to an increased rate of myopia incidence and myopia prevalence within the population. Recent estimates suggest that by 2050, about half (about 5 billion) of the world population will be myopic (Holden et al., 2016). Far from a futuristic and alarmistic prediction, there is already evidence that myopia prevalence has been increasing over the last decades, not only in Asia, but also in the USA (Vitale et al., 2009) and Europe (Williams et al., 2015). [...]